Growth Response and Color Brightening Enhancement of Cupang Fish (Betta sp.) Fed Yellow Pumpkin Extract (Cucurbita moscheta durch) - Meika Puspita Sari; Khusnul Khotimah; Lazeim Ramonda (Universitas Muhammadiyah Palembang, 2022)
This study aims to determine the effect of treatment on increasing the brightness of the color of ornamental fish (Betta Sp) during the feeding period and the growth response of toman fish during treatment. The treatment was pumpkin extract (Cucurbita moschetta Durch) mixed into pellet feed with various combinations. The color in fish is determined by connective tissue in the epidermis, which is the availability of pigments from pellets that can be bound and absorbed by the fish’s body. This research was carried out from August to October 2022 in the Laboratorium of Aquaculture. This study is an experimental method with a completely randomized design (CRD) with each treatment as follows, 10ml/100gr,20ml/100gr, and 30ml/100gr feed for 60 days. The results showed that adding pumpkin extract of 30ml/100gr could increase the color brightness of ornamental fish. Based on the results of the variance test, it showed a significant level of significant effect.